ALGORITMOS SUPERVISADOS PARA LA PREDICCIÓN DEL ANCHO DE BANDA DE LAS APLICACIONES EN AMAZON WEB SERVICE DESDE UNA PYME RURAL - Ramiro Osorio Diaz; Martha Yaneth Segura Ruiz; Mauricio Alonso Villalba (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2023)
This article presents a methodology to measure the bandwidth behaviour by making predictions of the network traffic thatconnects to the cloud in small and medium enterprises in rural areas with difficult access in Colombia, in order tooptimize network resources over time and ensure the quality of service in web applications. A comparative study of threeneural network algorithms that model a multilayer neural network is performed, selecting the one that has a minimumerror that approaches zero; the selected algorithm is trained from a data source to predict the network traffic thatconnects to the cloud.